A Short and medium term action plan for the international business sector 2009-2011 (The Division BridgetownBB, 2009)
Proposes a set of short to medium term policy, regulatory and marketing initiatives for the international business sector in Barbados in response to the expected global recessionary period.
Keywords: INTERNATIONAL TRADE